The prognostic impact of level I lymph node involvement in oropharyngeal squamous cell carcinoma. Issue 11 (30th August 2019) - Xiao, Roy; Ward, Matthew C.; Yang, Kailin; Adelstein, David J.; Koyfman, Shlomo A.; Prendes, Brandon L.; Burkey, Brian B.
Abstract: Background: We investigated the impact of level I lymph node involvement (LNI) on survival for patients with oropharyngeal squamous cell carcinoma (OPSCC). Methods: We performed a cohort study of patients with OPSCC who underwent resection with known human papillomavirus (HPV) status in the National Cancer Database (2010‐2014). Results: Among 5591 patients with OPSCC, 599 (10.7%) had level I LNI. Predictors of level I LNI included pT classification (pT3 vs pT1; odds ratio [OR], 1.95; P < 0.001), pN classification (pN3 vs pN1; OR, 1.63; P = 0.05), and level III LNI (OR, 6.05; P < 0.001). Among included patients, 4035 had known survival status. Level I LNI predicted inferior overall survival (OS) while adjusting for covariates (HR, 1.64; P < 0.001). Subset analyses revealed association between level I LNI and inferior OS among patients with base of tongue cancer, pT/pN classification greater than 1, and HPV‐negative cancer. Conclusions: Level I LNI predicts inferior OS, particular among patients with at least pT2 or pN2 OPSCC.